PERANCANGAN SISTEM INFORMASI DAILY CYCLE COUNT (SIDAC) BERBASIS WEB - Taufik, Andi; Ariani, Fattya (Universitas Lampung, 2023)
As a business actor in the field of health food and drink manufacturing, companies really need a warehouse as a means of storing their goods or products. This requires a calculation technique to keep the warehouse estimate running well. Basically, companies have used the Warehouse Management System (WMS) starting from receiving goods, storing them, and sending them. Because business processes are growing more and more incoming and outgoing transactions. This causes the need for a daily cycle count in the warehouse is urgently needed, because it is a benchmark for the accuracy of the stock in the warehouse according to or is well maintained or not. Utilization of the Warehouse Management System in the finish good warehouse in the company has not been able to overcome the need for a daily cycle count process as a need to maintain stock accuracy in the Warehouse. Based on these problems, a Daily Cycle Count information system is needed using a local web that can meet existing needs. The results of this study by making a daily cycle count application are able to help with stock accuracy problems in warehouses in finish good warehouses in the context of daily cycle count needs, as evidenced by the existence of a daily cycle count information system, stock accuracy in finish good warehouses can be maintained properly